Potential Of Used Cooking Oil As Dielectric Liquid For Oil-Immersed Power Transformers - Abu Bakar, Norazhar (IEEE, 2021)
This paper presents the potential of using treated used cooking oil as a potential dielectric liquid for high-voltage power transformers. The acidity of used cooking oil is higher than the prescribed limit of natural ester for power transformers. Hence, this paper proposes a combination of treatment methods to reduce the acidity of used cooking oil to less than 0.06 mg KOH/g. The treatment methods are: (1) alkaline refining, (2) bleaching and (3) synthetic silicate treatment. The physicochemical and electrical properties (acidity, color, density, flash point, viscosity, water content, breakdown voltage and dissipation factor) of the treated used cooking oil are measured according to standards. The results show that the acidity of the treated used cooking oil is 0.0182 mg KOH/g, which is 99.67% lower than the initial value of 5.4664 mg KOH/g. This acidity is achieved by implementing the following treatment methods: (1) alkaline refining using caustic soda (normality: 2.0N); (2) two cycles of bleaching with Fuller earth’s adsorbent (concentration: 10 wt%) in each cycle; and (3) treatment with synthetic silicate absorbent (concentration: 15 wt%). In addition, combined treatment methods affect the color rating of the treated used cooking oil, where the color rating is L0.5. The breakdown voltage and dissipation factor at 90 °C of the treated used cooking oil are found to be 100kV and 0.00688, respectively. The other physicochemical properties (density, viscosity and water content) of the treated used cooking oil fulfills the BS EN 62770 standard except for the flash point, with a value of 234 °C.